Evaluation of phosphate removal capacity of Mg/Al Layered Double Hydroxides from aqueous solutions - Guaya Caraguay, D. (2014)
In the present study, the adsorptive properties of phosphate on Mg/Al layered double hydroxides (LDHs) from aqueous solution were evaluated. The FTIR results confirmed the anionic exchange of the nitrate anions from the interlayer space with phosphate anions took place successfully. The kinetics experiments indicated that the kinetic models which best describe phosphate adsorption on LDHs are the pseudo-second order and intra-particle diffusion models. The effects of the pH and the amount of adsorbent on phosphate uptake were investigated and it was determined that the optimum conditions are pH 3 and 0.6 g/L LDH. The equilibrium isotherms showed that the phosphate uptake by Mg/Al LDH was in agreement with Freundlich model with constants of log Kf = 1.84 and 1/n = 0.52. The effect of interfering anions on the adsorption capacity was also evaluated in the presence of several competitive anions. The results showed that in presence of other ions phosphate ion uptake decreases in the order NO3 >HCO3- >Cl- >SO42. The desorption studies showed that the phosphate adsorbed on LDH is effectively desorbed at acid and basic pH values.